Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1021/om200407c
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of π- and n-Donor Bifunctional Monosubstituted Derivatives of Cyclopentadienylmanganese Tricarbonyl Complexes Containing an Allyl Group and Photo- and Thermoisomerization of the Corresponding Dicarbonyl Chelates

Abstract: Photochemical properties of a series of bifunctional monosubstituted derivatives of cymantrene containing a C-, N-, or O-bound π-allyl group, along with n-donating carbamate, amide, or pyridine fragments were investigated. The results obtained demonstrate that the nature and thermodynamic stability of the cyclopentadienylmanganese dicarbonyl chelates derived from bifunctional monosubstituted cymantrene derivatives depend substantially on both the nature of the functional groups and on their position in the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 29 publications
7
12
1
Order By: Relevance
“…IR monitoring of the irradiation of compounds 1 and 2 in benzene by a Hg lamp with λ = 365 nm showed that two MCO stretches of tricarbonyl complexes at 2019 and 1938 cm –1 disappear and two new bands of approximately equal intensities at 1931 and 1861 cm –1 appear in the ν(MCO) region of the IR spectra and the –NC=O band undergoes a low‐frequency shift of 54 cm –1 . The positions and intensity ratios are typical of the asymmetric and symmetric modes of MCO stretches in dicarbonyl complexes in which, according to our previous data,, , the manganese atom is coordinated to the –NC=O group; the low‐frequency shift of the ν(C=O) band also confirms the O ‐coordination. Thus, after photochemically induced CO loss, O ‐coordinated chelate complexes are formed (Figure , Scheme , Table ).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…IR monitoring of the irradiation of compounds 1 and 2 in benzene by a Hg lamp with λ = 365 nm showed that two MCO stretches of tricarbonyl complexes at 2019 and 1938 cm –1 disappear and two new bands of approximately equal intensities at 1931 and 1861 cm –1 appear in the ν(MCO) region of the IR spectra and the –NC=O band undergoes a low‐frequency shift of 54 cm –1 . The positions and intensity ratios are typical of the asymmetric and symmetric modes of MCO stretches in dicarbonyl complexes in which, according to our previous data,, , the manganese atom is coordinated to the –NC=O group; the low‐frequency shift of the ν(C=O) band also confirms the O ‐coordination. Thus, after photochemically induced CO loss, O ‐coordinated chelate complexes are formed (Figure , Scheme , Table ).…”
Section: Resultssupporting
confidence: 73%
“…It is also well known that one of the basic properties of cyclopentadienyltricarbonyl manganese (cymantrene) complexes is the possibility of ligand exchange at the manganese atom under UV irradiation leading to a significant change in the spectral properties of the molecules . Earlier we found that the photolysis of cymantrenylalkylamides of carboxylic acids results in the formation of thermodynamically stable dicarbonyl chelates due to the coordination of the carbonyl fragment –NC=O to the Mn atom.…”
Section: Introductionmentioning
confidence: 87%
“…The olefin chelates 19 and 21 were isolated as oils; the 1 H NMR spectra of these compounds confirm their structures and are in good agreement with the spectra of related olefin chelates , …”
Section: Resultssupporting
confidence: 64%
“…The irradiation of a solution of 5 in benzene or THF results simultaneously in the formation of both chelate 19 with ν(CO) at ν̃ = 1975 and 1917 cm –1 and its isomer 20 with ν(CO) at ν̃ = 1930 and 1857 cm –1 in benzene (Scheme ). The band assignment in this region is based on our previous results , . For allylamides 6 – 8 , the simultaneous formation of olefin ( 21 – 23 ) and amide ( 24 – 26 ) chelates in ratios of 2:1 is observed in benzene.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation